Perinatal outcomes after stimulated versus natural cycle IVF: a systematic review and meta-analysis. Issue 1 (January 2018) - Kamath, Mohan Shashikant; Kirubakaran, Richard; Mascarenhas, Mariano; Sunkara, Sesh Kamal
Abstract: Pregnancies resulting from assisted reproductive techniques are at higher risk of adverse perinatal outcomes compared with spontaneous conceptions. Underlying infertility and IVF procedures have been linked to adverse perinatal outcomes. It is important to know if ovarian stimulation influences perinatal outcomes after IVF. A systematic search for relevant studies was conducted up to November 2016 on the following databases: PubMed, EMBASE, DARE and Cochrane Central Register of Controlled Trials . Perinatal outcomes included preterm birth (PTB), low birth weight (LBW), small for gestational age (SGA), large for gestational age (LGA) and congenital anomalies. Data from four studies, which included a total of 96, 996 and 704 singleton live births after stimulated IVF and natural or modified natural cycle IVF, were included in the meta-analysis. The risk of PTB (RR 1.27, 95% CI 1.03 to 1.58) and LBW (RR 1.95, 95% CI 1.03 to 3.67) were significantly higher after stimulated compared with natural or modified natural cycle IVF. Data from one study were available for SGA, LGA, congenital anomalies and no significant differences were reported between the groups. This study suggests a higher risk of PTB and LBW after stimulated IVF compared with natural or modified natural IVF, although the absolute increase in risk may be low.